Utilization of Papain Enzymes on the Production of Virgin Coconut Oil - Sabbila, Syifa Ranggita; Broto, R. T. D. Wisnu (Journal of Vocational Studies on Applied Research, 2022)
VCO is an oil that has many benefits for the human body. In the health sector, VCO can function to increase the human body's resistance and accelerate the healing of diseases and obesity. Making VCO can be done in various ways, one of which is by enzymatic method with the help of papain enzymes. The purpose of this study was to determine the most influential variable on the making of virgin coconut oil. The method used is by fermentation using papain enzyme catalysts and the temperature and time of fermentation according to the specified variable and analysis of water content and free fatty acids using factorial design 2x3. The results obtained from the study of the most influential effect on water content and free fatty acids are time variable and enzyme concentration, while the most influential interaction variables are fermentation time and temperature. The optimum water content obtained is 0.18% and free fatty acids are 0.28%. The optimum combination of independent variables that can produce optimum water content and free fatty acids is papain enzyme concentration of 3gr, temperature 33oC, and fermentation time of 24 hours.